Pengaruh Kewajiban Moral dan Akuntabilitas Pelayanan Publik terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan pada Badan Pengelola Pajak dan Retribusi Daerah (BPPRD) Simpang Empat - Sovianum, Sovianum; Lubis , Fauzi Arif; Nurwani, Nurwani (Medan Resource Center, 2023)
This article aims to determine the effect of moral obligation and public service accountability on taxpayer compliance with case studies at the Regional Tax and Retribution Management Agency (BP2RD) Simpang Empat. This study used quantitative methods and associative approaches, data collection techniques using questionnaires and the population and sample in this study were 100 people. Data were analyzed by multiple linear regression method. The positive results of this study indicate that the Moral Obligation variable has a significant effect on Taxpayer Compliance, variable Public Service Accountability has a significant and significant effect on Taxpayer Compliance, and the variables of Moral Obligation and Public Service Accountability have a simultaneous and significant effect on Taxpayer Compliance. This can be seen from the test of the coefficient of determination where variations of the Moral Obligation and Service Accountability variables are able to explain the Taxpayer Compliance variable by 72.4%.